On a new genus and species of euryplacid crab (Crustacea: Decapoda: Brachyura: Goneplacoidea) from the Philippines - Ng, Peter K.l.; Castro, Peter (Zootaxa, 2007)
A new genus and new species of euryplacid crab (Brachyura, Goneplacoidea) is described from the Philippines. It superficially resembles species of Carcinoplax H. Milne Edwards, 1852 (Goneplacidae) but the structure of the sternum, abdomen, and gonopods show that it is a euryplacid. Comparisons are made with Eucrate De Haan, 1835.